Exomic and epigenomic analysis of pulmonary blastoma - Alirezaie, Najmeh; Chong, Anne-Laure; Kommoss, Felix; Sabbaghian, Nelly; Camacho Valenzuela, Jose; Pelletier, Dylan; Nadaf, Javad; Kolekar, Shailesh B.; Sivapalan, Pradeesh; Evans, Mark G.; Thorner, Paul S.; Fiset, Pierre-Olivier; et al. (Lung cancer, 2024)
Objective - Pulmonary blastoma is a rare, biphasic, adult-onset lung tumor. In this study, we investigate whether DICER1 pathogenic variants are a feature of pulmonary blastomas through in-depth analysis of the molecular events defining them. - Methods - We performed exome-wide sequencing and DNA methylation profiling of 8 pulmonary blastomas from 6 affected persons. - Results - We identified biallelic somatic DICER1 pathogenic variants in 7 of 8 cases. The remaining case had a solitary missense pathogenic variant in the RNase IIIb domain of DICER1. Six of 8 cases carried a CTNNB1 hotspot variant and 4 of 8 had a somatic pathogenic variant in TP53. Methylation analysis showed that the pulmonary blastomas clustered with other DICER1-mutated tumors and not with other more common types of lung cancer. - Conclusion - We conclude somatic DICER1 pathogenic variants are the major driver of pulmonary blastoma and are likely to act in conjunction with CTNNB1 hotspot variants that are often present.
Online verfügbar: 5. August 2024, Artikelversion: 8. August 2024
Gesehen am 10.07.2025